Magnitude of unreported kala-azar cases in a highly endemic district of Bihar, India: A positive impact of Indian elimination programme - N A Siddiqui; K Pandey; V N R. Das; S K Sinha; R B Verma; C S Lal; V Ali; R K Topno; M R Dikhit; P Das (Journal of Vector Borne Diseases, 2019)
Background & objectives: In India, kala-azar surveillance is weak and no public-private partnership exists for disease containment. Estimate of disease burden is not reliably available and still cases are going to private providers for the treatment. The present study aimed to assess the magnitude of kala-azar cases actually detected and managed at private set-up and unreported to existing health management information system. Methods: Institution based cross-sectional prospective pilot study was conducted. List of facilities was created with the help of key informants. The information about incidence of kala-azar cases were captured on monthly basis from July 2010 to June 2011. Rapid diagnostic strip test (rk-39) or bone marrow/splenic puncture were applied as laboratory methods for the diagnosis of kala-azar. Descriptive statistics as well as chi-square test for comparison between proportions was conducted. Results: Overall availability of private practitioners (PPs) was 4.59/1,00,000 population and maximum PPs (46; 93.9%) were from qualified category. The median years of medical practice was 25 yr (inter quartile-range [18, 28]). Interestingly, only a small proportion (240; 19%) of cases was managed by PPs. Amongst the PPs, only low proportion (32; 18.2%) managed >2 cases per month. The mean number of kala-azar suspects and cases identified varied significantly between different PPs’ professions with p <0.048 and p <0.032, respectively. A highly significant difference (p <0.0001) was observed for kala-azar case load between qualified and unqualified practitioners. A small proportion (38; 15.8%) of kala-azar cases was not present in the public health system record. Interpretation & conclusion: Still sizeable proportions of cases are going to PPs and unrecorded into government surveillance system. A mechanism need to be devised to involve at least qualified PPs in order to reduce treatment delay and increase case detection in the region.